Plato and intellectual development: a new theoretical framework emphasising the higher-order pedagogy of the Platonic dialogues - Saracco, Susanna (Palgrave Macmillan, 2020)
This book reconstructs the impact of Plato's words for the modern reader. In the Republic, Plato presented his schematization of human intellectual development, and called for collaboration between writer and reader. The response presented in this book results in a new theoretical framework for engaging with Plato's dialogues. Susanna Saracco analyzes the epistemic function of Plato's written words and explores Plato's higher order pedagogy, in which students are not mere learners and teachers are not the depositories of the truth